“The Presentation”: an intensive arts-based rite of passage adapted for the training of Music Therapists. - Faire, Rosemary Julea (Voices: A World Forum for Music Therapy, 2012)
This paper is firstly a story, told by both my students and myself. It started with my question: can arts other than music be used by Music Therapy students to negotiate uncertainties which arise at the threshold of entering into their new therapist community? A rite of passage from Expressive Arts Therapy in Toronto and Switzerland was transplanted into an Australian Music Therapy course. What emerged was truly magical. The students began by asking themselves defining questions… where am I now?…where do I want to be? They let art-works emerge from their growing edges to provide sometimes surprising answers. They then formed small groups and allowed the art-works to interact to create a Presentation - a ritual day of exchanging art-gifts. Their written reflections help illustrate the story. They describe “openness to possibilities”, “unexpectedness”, “like flying”, “a healing process”, “belonging”, “reverence”. Afterwards, in my own reflections, I attempt to grapple with the significance of such experiences in which we enter, through art-making, into the realm of “poiesis”. Are they vital to counterbalance the evidence-based approaches to knowing? What are the ramifications for an inquiry-based Music Therapy practice which values “not-knowing”? Can we deepen our courage to dwell in the discomfort of not-knowing while knowing finds us?